Viral RNA-Dependent RNA Polymerase Inhibitor 7-Deaza-2'-C-Methyladenosine Prevents Death in a Mouse Model of West Nile Virus Infection - Eyer, Luděk; Fojtíková, Martina; Nencka, Radim; Rudolf, Ivo; Hubálek, Zdeněk; Ruzek, Daniel (Antimicrobial agents and chemotherapy, 2019)
West Nile virus (WNV) is a medically important emerging arbovirus causing serious neuroinfections in humans and against which no approved antiviral therapy is currently available. In this study, we demonstrate that 2'-C-methyl- or 4'-azido-modified nucleosides are highly effective inhibitors of WNV replication, showing nanomolar or low micromolar anti-WNV activity and negligible cytotoxicity in cell culture. One representative of C2'-methylated nucleosides, 7-deaza-2'-C-methyladenosine, significantly protected WNV-infected mice from disease progression and mortality. Twice daily treatment at 25 mg/kg starting at the time of infection resulted in 100% survival of the mice. This compound was highly effective, even if the treatment was initiated 3 days postinfection, at the time of a peak of viremia, which resulted in a 90% survival rate. However, the antiviral effect of 7-deaza-2'-C-methyladenosine was absent or negligible when the treatment was started 8 days postinfection (i.e., at the time of extensive brain infection). The 4'-azido moiety appears to be another important determinant for highly efficient inhibition of WNV replication in vitro However, the strong anti-WNV effect of 4'-azidocytidine and 4'-azido-aracytidine was cell type dependent and observed predominantly in porcine kidney stable (PS) cells. The effect was much less pronounced in Vero cells. Our results indicate that 2'-C-methylated or 4'-azidated nucleosides merit further investigation as potential therapeutic agents for treating WNV infections as well as infections caused by other medically important flaviviruses.
Keywords: tubercidin; antiviral agents; prasata; RNA-dependentní RNA-polymerasa; západonilská horečka; Swine; modely nemocí na zvířatech; Cell Line; flavivirus; West Nile Fever; Cercopithecus aethiops; replikace viru; progrese nemoci; West Nile virus; nucleoside analogs; antivirové látky; Tubercidin; myši inbrední BALB C; Disease Progression; Chlorocebus aethiops; Mice, Inbred BALB C; Animals; Antiviral Agents; RNA-Dependent RNA Polymerase; Viremia; ženské pohlaví; Virus Replication; zvířata; virus západního Nilu; Disease Models, Animal; myši; buněčné linie; Vero Cells; viremie; Mice; Female; Vero buňky